Electronic Procurement of Government Goods and Services from the Perspective of Islamic Jurisprudence - Iqmi Qaisah Ali; Oman Fathurohman SW (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Fraud and corruption in the procurement of government goods and services remain major contributors to the level of corruption in Indonesia. Transparency and accountability are key principles in reducing fraud and corruption in the procurement process. The government currently mandates the implementation of e-purchasing for goods and services related to meeting national and/or strategic needs as determined by the minister, head of an agency, or regional head. In addition to increasing transparency and accountability, e-purchasing is expected to enhance efficiency and reduce transaction costs. However, in practice, the e-purchasing process has not yet been ideally implemented according to legal standards. Therefore, this research aims to examine the transaction process in e-purchasing from the perspective of fiqh muamalah and the issues surrounding the implementation of e-purchasing. This research is aimed at assessing and finding common ground between the e-purchasing mechanism for government procurement of goods and services and the principles of fiqh muamalah. This research is a literature study with a qualitative approach, in which the researcher gathers various information regarding the electronic procurement of government goods and services, then aligns it with the concepts in fiqh muamalah. The transaction mechanism in e-purchasing resembles that of online buying and selling, and its original ruling is permissible (mubah) as long as it does not violate Islamic law. Generally, the contracts used in these transactions are the bai' salam and ijarah contracts.